Regional innovation: State of the art in the Észak-alföld region - Berde, Ágnes Barbara (Acta Agraria Debreceniensis, 2011)
Innovation and innovation performance is gaining increasing importance in European policy, as the targets determined by the Lisbon priorities related to innovation seem to be still far away from the reality in some European countries and at EU level as well. Although the economic crisis determined the priorities of economic development and made it more complicated to dedicate more budget of Research and Development, one of the five ambitious objectives of the EU’s growth strategy for the coming decade: Europe 2020: A strategy for smart, sustainable and inclusive growth is still focusing on innovation. As the Lisbon Strategy determined the paths for national targets in the given areas, Europe 2020 will be adopted as well by the Member States. In this context, the current work would like to give a short overview how Lisbon Strategy effected the national and regional innovation system in Hungary and will analyze its impact on Észak-Alföld’s region Research, Development and Innovation performance in the recent years and the transition of regional innovation governance system.